New typology of women’s strategies to strengthen their managerial decision-making power in wheat in India - CGIAR Research Program on Wheat (2020)
The new typology will allow researchers and development partners to better understand empowerment dynamics and women’s agency. The typology can be used to distinguish between the ways women (and men) express their ideas and get to where they want.